The Political Economy of Preference Falsification: Timur Kuran's Private Truths, Public Lies - Frank, Robert H. (Journal of Economic Literature, 1996)
Private Truths, Public Lies is a splendid book. It tackles a long list of interesting and important questions that have been discussed at length, and largely unsuccessfully, by scholars from each of the social sciences. Kuran blends the insights of economics, psychology, sociology, and political science into a behavioral model that moves the discussion forward on many fronts. His may not be the model that many traditional economists might have chosen, but it is one that most can live with.